2016
DOI: 10.1089/rej.2015.1801
|View full text |Cite
|
Sign up to set email alerts
|

YiQiFuMai Powder Injection Attenuates Ischemia/Reperfusion-Induced Myocardial Apoptosis Through AMPK Activation

Abstract: The YiQiFuMai powder injection (YQFM), a traditional Chinese medicine (TCM) prescription re-developed based on the well-known TCM formula Sheng-maisan, showed a wide range of pharmacological activities in cardiovascular diseases in clinics. However, its role in protection against myocardial ischemia/reperfusion (MI/R) injury has not been elucidated. The present study not only evaluated the cardioprotective effect of YQFM from MI/R injury but also investigated the potential molecular mechanisms both in vivo and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Consistent with our previous study10, the present study demonstrated the protective effect of Shengmai preparations YQFM on MI/R injury. Similar to YQFM, the active ingredients combination GRS also exerted cardioprotective effect with the same potency, as shown by improved LV function, decreased infarct size, cell viability loss and LDH activities.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with our previous study10, the present study demonstrated the protective effect of Shengmai preparations YQFM on MI/R injury. Similar to YQFM, the active ingredients combination GRS also exerted cardioprotective effect with the same potency, as shown by improved LV function, decreased infarct size, cell viability loss and LDH activities.…”
Section: Discussionsupporting
confidence: 93%
“…At the end of the experiment, blood was collected and serum was separated by centrifugation, the LDH was detected as previously described10. After collecting the blood samples, the hearts were removed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatments consisting of multiple drugs directed against multiple pathways and targets have stronger therapeutic efficacy for complex multifactorial diseases [ 7 , 8 ]. The effective evidence from clinical trials contributes to the acceptance of TCM can be useful in the treatment of cardiovascular diseases [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%